الرباعي المكرر ومشتقاته في القرآن الكريم " دراسة صوتية دلالية" - قمرة, كرام (جامعة الوادي - University of Eloued, 2021)
ملخص: تتعد مظاهر الإعجاز الصرفي في القرآن الكريم، ومن بينها تلك الألفاظ ذات البنية الرباعية المكررة، والتي توحي صيغتها الصرفية ، وصورتها الصوتية بدلالتها اللغوية والتركيبية داخل السياق القرآني. فهي ألفاظ قوية تشعرك بالاهتزاز والتكرير لفظا ومعنى، مما يشير إلى تَفَرُّدِ اللفظة القرآنية في مبناها ومعناها وتشكيلها الصوتي . Abstract: The aspects of the morphological miraculousness are numerous in the Holy Quran. This can be apparent in the recursive quadric-radical-structured morphemes, whose morphological structure and sound image express its linguistic and componential significance within the Quranic context. These words are so strong giving a sense of voicing and recursion whether in structure or in significance, which points to the uniqueness of the Quranic morphemes in their structure, significance as well as in their sound formation.
Keywords: الرباعي المكرر ; الألفاظ الاهتزازية ; الإعجاز الصرفي ; الأبعاد الدلالية ; الدلالة الصوتية ; المقطع الصوتي; The Recursive quadruple ; voicing ; morphological miraculousness ; semantic dimensions, phonemic connotation ; phonetic syllable